FIRST RECORD OF Gotocotyla acanthura ON THE GILLS OF Katsuwonus pelamis IN THE SOUTHWESTERN ATLANTIC OCEAN - SILVA, Claudio Giovanio da; LIMA, José Ticiano Arruda Ximenes de; FIGUEIREDO, Naibe Cristina de (Ciência Animal, 2023)
Little is known regarding the geographical distribution of parasites in marine environments and monogenea are parasites that tend to exhibit host specificity and are commonly found on fins, body skin, gills, chambers branchial, oral cavity, cornea and nostrils of the host. Currently, the genus Gotocotyla has seven described species, with fish in the genus Scomberomorus being the natural hosts. This study reports, for the first time, Gotocotyla acanthura on a new host, skipjack tuna (Katsuwonus pelamis), in Brazil, Southwest Atlantic Ocean. One hundred two Skipjack tuna (K. Pelamis) were acquired between the months of collection and examined for monogenean parasites. Gotocotyla acanthura was identified with ecological indexes including prevalence (11.76), mean intensity (1.55±0.53) and mean abundance (0.14±0.47).